ANALYSIS OF (G/M/C):(FIFO/C/?)- ERLANG B QUEUEING SYSTEM ON BED FOR COVID-19 PATIENTS AT HOSPITAL IN ARCAMANIK SUB CITY AREA - El'haq, Melinda
When the service capacity is unable to serve but customers keep arriving, it creates a queue that makes customers have to wait. Apart from waiting, customers can be rejected from the system (balking). The data used as customer arrivals is the increase in positive cases of COVID-19 patients in Arcamanik Sub City Area (SCA), from September 17th, 2020 to February 4th, 2021. Arcamanik SCA is often included in one of the highest positive cases of COVID-19 in Bandung City. The server used is the number of beds in the Hermina Arcamanik Hospital. The method used is a discrete event simulation, with a queuing model (G / M / c):( FIFO / c / ?)- Erlang B. The more servers, the chances of customers being rejected will converge to zero. The minimum required bed is 32 beds, so patients who come are not rejected. Refused patients can visit another hospital as an alternative, namely RSHS. The proportion of beds for patients from Arcamanik SCA is 0,16 times of the excess empty bed. In order for patients to receive treatment at the two hospitals, the number of cases COVID-19 must not exceed 62 cases.